PETROLOGIC EVOLUTION OF LARGE FAILED RIFTS IN THE EASTERN PACIFIC: PETROLOGY OF VOLCANIC AND PLUTONIC ROCKS FROM THE MATHEMATICIAN RIDGE AREA AND THE GUADALUPE TROUGH - Batiza R.; Vanko D.A. (My University, 1985)
The Mathematician failed rift was a fast spreading oceanic ridge prior to abandonment about 6.5 Ma. but presently has the morphology of a slow spreading ridge crest. Dredges of its inner rift valley walls indicate that it also has the petrologic characteristics of a slow-spreading ridge: the dredges recovered serpentinized peridotite, cumulate and isotropic gabbro, diabase and mid-ocean ridge basalt (MORB) lava. The gabbros include fresh troctolites, cpx gabbros and two pyroxene gabbros, all of which have relatively iron-rich mafic minerals and sodic plagioclase. Other gabbro samples are sheared and metamorphosed and presently have lower greenschist to lower amphibolite mineral assemblages. Peak metamorphic temperatures calculated from coexisting amphibole and plagioclase are about 600 C at 1-2 kb pressure but many of the assemblages reflect much lower temperatures. The MORB lavas from the rift valley walls are relatively fresh and very primitive (100 Mg/(MgFe2) = 72−74). This suggests that they were erupted in the last stages of rift abandonment after the disappearance of the shallow crustal magma chamber that may have been present when the rift was a fast-spreading one. One dredge of the Guadalupe failed rift also recovered MORB lava, but it is more evolved than that at the Mathematicians. Dredges of failed transform faults in the Mathematicians recovered fresh alkali basalt. This post-abandonment alkali basalt may be analogous to alkalic lavas erupted off-ridge near active spreading ridges like the East Pacific Rise. Dredges of an E-W bathymetric linear feature near the Mathematician ridge south of the Clarion fracture zone also recovered very fresh alkalic lavas. These are distinct from the post-abandonment alkalic rocks in the Mathematicians and include hawaiites and trachytes, some of which were ‘popping’ when first brought to the surface. We conclude that in some cases of fast-spreading rift abandonment, the rift first slows down and ceases to have a steady state magma chamber in the crust. This is followed by the eruption of alkali basalts at failed transforms as the lithosphere thickens in place.